beta Phase transformations in the Cu-11mass%Al alloy with Ag additions - Magdalena, A. G. [UNESP]; Adorno, A. T. [UNESP]; Carvalho, T. M. [UNESP]; Silva, R. A. G. (Springer, 2011)
In the Cu-Al system, due to the sluggishness of the beta a dagger" (alpha + gamma(1)) eutectoid reaction, the beta phase can be retained metastably. During quenching, metastable beta alloys undergo a martensitic transformation to a beta' phase at Al low content. The ordering reaction beta a dagger" beta(1) precedes the martensitic transformation. The influence of Ag additions on the reactions containing the beta phase in the Cu-11mass%Al alloy was studied using differential scanning calorimetry and in situ X-ray diffractometry. The results indicated that, on cooling, two reactions are occurring in the same temperature range, the beta -> (alpha + gamma(1)) decomposition reaction and the beta -> beta(1) reaction, with different reaction mechanisms (diffusive for the former and ordering for the latter) and, consequently, with different reaction rates. For lower cooling rates, the dominant is the decomposition reaction and for higher cooling rates the ordering reaction prevails. on heating, the (alpha + gamma(1)) -> beta reverse eutectoid reaction occurs with a resulting beta phase saturated with alpha. The increase of Ag concentration retards the beta -> (alpha + gamma(1)) decomposition reaction and the beta -> beta(1) ordering reaction, which occurs in the same temperature range, becomes the predominant process.
Keywords: Thermal behavior; Eutectoid decomposition; Martensitic transformation; Cu-Al-Ag alloys